Focus on the Narrative Skills of Teenagers With Developmental Language Disorder and High Functioning Autism - Broc, Lucie; Brassart, Elise; Bragard, Anne; Olive, Thierry; Schelstraete, Marie-Anne (Frontiers in Psychology, 2021)
Purpose. Narratives of personal experiences emerge early in language acquisition and are particularly commonly experienced in children's daily lives. To produce these stories, children need to develop narrative, linguistic and social-cognitive skills. Research has shown that these skills are impaired in children with developmental language disorder (DLD) and high functioning autism (HFA). Aim. This study aimed to determine whether narrative skills are still impaired in adolescence and to highlight the language similarities and differences between teenagers with DLD and HFA in the production of a narrative of a personal experience. Method. Ten teenagers with DLD, 10 teenagers with HFA and 10 typically developing (TD) teenagers, matched on chronological age, told a narrative of a personal experience. These stories were analyzed to evaluate narrative skills through coherence (respect of the narrative schema) and cohesion (anaphora and connectors) and social-cognitive skills (affective and cognitive mental states of the characters, and arbitrary vocalizations such as voice noises). Results. Teenagers with DLD were less compliant with the complication step in the narrative schema than teenagers with HFA or TD. No difference was observed between the three groups of teenagers in terms of cohesion or regarding the positive and negative social-cognitive skills used in narratives. Conclusions. When producing a narrative of a personal experience, HFA teens do not have difficulties neither with narrative skills and with social-cognitive skills assessed in this paper. In DLD the profile of the teens is not the same. If they do not have difficulties with social-cognitive skills and with a part of narrative skills (cohesion), they have difficulties with the narrative schema